INCREASING PEDAGOGICAL COMPETENCE THROUGH OPTIMIZATION OF TEACHERS’ ACADEMIC SUPERVISION AT SMP NEGERI 11 DUMAI - Leni Suryani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of teachers’ pedagogical competence through optimizing academic supervision. Establishing educational programs without being accompanied by the ability of educators is meaningless. A good educator is knowledgeable. Educators would like to complete their obligations intentionally if they have pedagogical competence because each teacher’s obligation requires a variety of abilities. Competence is the ability or people’s capability to do something based on their ability. Meanwhile, pedagogy is an ability that must be owned by educators (padagoc), which is in terms of teachers, with various planned actions to educate (pedagogy) such as planned activities in the process of learning activity management at schools that require certain abilities from teachers and an effort to transform the science (pedagogic) towards students. The research is a school action research (PTS), which aims to determine the success of increasing teachers’ pedagogical competence in teaching through the utilization of audio-visual media at SMP Negeri 11 Dumai. Based on the results of the analysis and discussion, it can be concluded that the percentage of teachers’ pedagogical competence was 63% in the first cycle with the good category and increased to 82% in the second cycle with the good category. Thus, the optimization of academic supervision to improve the teachers’ pedagogical competence at SMP Negeri 11 Dumai is successful.